2020
DOI: 10.1590/1413-81232020252.15232018
|View full text |Cite
|
Sign up to set email alerts
|

Custos de produtividade entre pessoas envolvidas em acidentes de trânsito

Abstract: Resumo Este artigo objetivou caracterizar os custos de produtividade de pessoas envolvidas em acidente de trânsito (AT) em um município de médio porte. Um estudo longitudinal de base domiciliar foi realizado entre 2013 e 2015. Neste período, foram entrevistados e acompanhados indivíduos com AT e calculados os custos de produtividade. Os valores mensurados e estimados foram considerados para cálculo dos valores brutos e per capita e ajudaram a constituir os custos de perda de produtividade (dias sem trabalhar) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
1
0
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 16 publications
0
1
0
3
Order By: Relevance
“…There is a limited number of studies that assess productivity loss due to all causes of death, particularly on the African continent. In addition, most studies found analyzed costs due to specific causes [17,[27][28][29][30][31][32][33]. Furthermore, no studies were found that addressed the issue of productivity loss in small island developing countries, such as Cabo Verde.…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…There is a limited number of studies that assess productivity loss due to all causes of death, particularly on the African continent. In addition, most studies found analyzed costs due to specific causes [17,[27][28][29][30][31][32][33]. Furthermore, no studies were found that addressed the issue of productivity loss in small island developing countries, such as Cabo Verde.…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…Por otra parte, la mediana de costos por siniestro de tránsito fue de US$ 56 (RI = 29,35-140,15) y el promedio 290,11 ± 731,22 (IC95% 239,74-340,48) correspondiente solo a los gastos médicos derivados de su permanencia en el hospital, podría considerarse como un costo bajo comparado con el estudio realizado en Irán donde el promedio del costo está en US$ 9,024 11 , pero se debe tener en cuenta que en nuestro estudio no se incluyeron costos indirectos, costos por pérdida de productividad derivada del accidente que, según otros estudios, pueden ser más altos que los netamente relacionados a la atención en salud debido al accidente 15,18,19 .…”
Section: Discussionunclassified
“…La mortalidad por esta problemática fue de 18,3, y los años de vida perdidos fueron 817,4 por cada 100.000 habitantes 2 . En Colombia, durante el año 2019 la tasa de siniestros de tránsito fue de 1.214, con tasa de mortalidad de 14,6 (IC95% 11,[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]6) por 100.000 habitantes, esta última corresponde al 3,13% del total de muertes en el país, posicionándose en la novena causa de muerte. La mortalidad es mayor en hombres con 24 por 100.000 hab.…”
Section: Introductionunclassified
“…The World Health Organization reports that over 1.35 million people die yearly due to road traffic crashes, while 20 to 50 million sustain non-fatal injuries [6,7]. These crashes are a leading cause of death and injury worldwide, resulting in billions of dollars in medical expenses, property damage, and lost productivity [8,9]. Beyond the monetary costs, crashes can also cause lasting psychological trauma for survivors and their families [10,11].…”
Section: Introductionmentioning
confidence: 99%